Design and simulation of low actuation voltage RF MEMS shunt capacitive switch with serpentine flexures&rectangular perforations - Jayavardhani, K; K. Noureen Fathima, S; Bhima Sankar, K; Kavya Sri, K; Sunithamani, S (International Journal of Engineering and Technology, 2018)
This paper presents the design and simulation of RF MEMS shunt capacitive switch with low actuation voltage, low insertion loss and high isolation. Actuation voltage depends on the parameters like air gap, spring constant and actuation area. In this design, we have proposed a serpentine meander structure to reduce the spring constant of the beam thus reducing actuation voltage. The rectangular perforation is used to reduce the squeeze film damping by decreasing the mass of the switch. The proposed switch has attained a low actuation voltage of 4.5V for a displacement of 0.84Î¼m. The air gap between the beam and the dielectric is 1Î¼m. This radio frequency (RF) MEMS shunt switch is designed and simulated using COMSOL Multiphysics 5.2. The RF performance of the shunt switch is analyzed in Ansoft HFSS 13 and the results show that the return loss was about -13.50 dB at 20GHz in the OFF state and -8.5 dB at 18 GHz in the ON state. A high isolation of -36.00 dB was achieved in the OFF state at a frequency of 5GHz and a low insertion loss is obtained. The results show that the switch is suitable for wireless applications operating in the frequency range from 5 to 20GHz.Â